The Effect of Timeliness, Transparency, and Effectiveness of Recommendations on Audit Quality (Study at the Audit Board of Southeast Sulawesi Province) - Sitti Namira Hasanuddin; Ishak Awaluddin; Intihanah Intihanah (PT. Banjarese Pacific Indonesia, 2025)
This study aims to analyze the influence of timeliness, transparency, and the effectiveness of recommendations on audit quality at the Audit Board(BPK) of Southeast Sulawesi Province. The research focuses on an economic-financial perspective, namely how these three variables play a role in improving the efficiency of fiscal governance, public spending accountability, and the effectiveness of state financial oversight. Research data were obtained through questionnaire distribution and audit document analysis. The results show that timeliness has a significant effect on audit quality because it is able to maintain the relevance of findings and accelerate follow-up. Transparency has a significant effect on increasing public trust and auditor credibility. The effectiveness of recommendations has the strongest influence on audit quality because it determines the implementation of financial governance improvements in audited entities. This study emphasizes the importance of promoting a fast, open, and responsive audit system to improve the quality of state financial management